The Model-Lead-Test (M-L-T) Approach in Teaching Physical Education Among Grade 9 Students: Basis for A Training Design - Silmaro, Glenda B. (RIRAI Publisher, 2025)
The study aimed to investigate the effectiveness of the Model-Lead-test (M-L-T) approach on the academic performance and attitude towards Physical Education of Grade 9 students at Jacinto D. Malimas Sr. National High School, Odiongan, Gingoog City for the school year 2023-2024. The study used a quasi-experimental research design. The experimental group (n=36) was exposed to the Model-Lead-Test approach, while the control group (n=36) under the lecture method. The research instruments used were the Pre and Post summative test, Performance tasks Rubrics and the Students’ Attitude Towards Physical Education (PE) questionnaire. Frequency counts and percentage, weighted mean, Mann-Whitney U Test and Paired t-test were utilized in analyzing the data. The findings showed that the learners exposed to the M-L-T approach performed better (m=5.52) than those under the non-MLT (mean=3.33). It was also shown that more students (77.7%) achieved very good performance tasks under M-L-T approach than those under the non MLT (8.3%). In addition, there were more students who achieved excellent performance (f=14, 38.89%) under M-L-T than those under the non-M-L-T approach (f=6; 16.67%). Such results led to a significant difference (t=12.67, p=.000) in the academic performance of the participants. The program design based on the M-L-T approach utilized models and demonstrations as learning tools, providing students with clear, visual guidance, facilitating better understanding, and skill acquisition.